Failure behaviour of the adhesive layer and angle ply composite adherends in single lap joints: A numerical study. (December 2018) - Demiral, Murat; Kadioglu, Ferhat
Abstract: In the last decades, composite materials have been increasingly used in advance engineering fields such as aerospace and automobile industries due to their advantages in terms of stress concentrations, structural weight and manufacturing. Joining composite parts in such applications has been increasingly achieved by adhesives compared to welded, riveted or bolted connections. Mechanical testings of adhesively bonded composite joints are often time consuming and expensive due to a number of parameters involved and their analytical modellings are complicated. Therefore, numerical analysis is increasingly used in recent years to overcome these limitations. In this work three-dimensional FE modelling of the single lap joints (SLJs) of angle ply composite adherends subjected to tensile loading was developed using ABAQUS/Explicit. Cohesive zone model was adopted for the modelling of damage in the adhesive layer. The continuum damage mechanic model implemented via a user defined VUMAT subroutine was used to model the intraply damage in composite adherends. The model accounted for the damage initiation, the damage evolution, and the nonlinear shear behaviour of the material. Experiments of the SLJs of [±10]5s, [±20]5s, [±45]5s and [±55]5s adherends under tensile loading were performed. The adherends were manufactured from glass reinforced polymer matrix and the adhesive layer was AF163-2K. For verification of the developed model, numerical results were compared with those of the experiments mentioned above. The SLJs of [±10]5s and [±20]5s adherends failed due to failure in the adhesive layer and those of [±45]5s and [±55]5s failed mainly due to failure in the adherends. The peel and shear deformation modes in the adhesive layer were invoked in different ways for different SLJ configurations. The effects of adhesive layer thickness and the overlap length on the response of the SLJ were investigated in detail.